Understanding Fraudulent Financial Reporting Techniques: Analysis of Public Company Cases - Dalkılıç, Ali Fatih (International Journal of Contemporary Economics and Administrative Sciences, 2018)
Earnings management is the active manipulation of accounting results for the purpose of creating an altered impression of business performance. It is an intentional structuring of reporting or production and investment decisions around the bottom line impact.Earnings management is the taking deliberate steps within the constraints of generally accepted accounting principles to bring about a desired level of reported earnings. Aim of the study is to explain some techniques in detail and to present real life public company cases.